2017
DOI: 10.1007/s10068-017-0090-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various ginsenosides and ginseng root and ginseng berry on the activity of Pancreatic lipase

Abstract: Although ginsenosides Rb1, Rb2, Rc, and Rd and ginseng extracts are shown to inhibit pancreatic lipase (PL) activity, the effects of the other ginsenosides, particularly the deglycosylated ones that are considered to show stronger biological activities than the glycosylated forms, are not clear. In this study, we observed the effects of various ginsenosides on PL activity. Results showed that the effects vary with each individual ginsenoside. Ginsenosides Rb1, Rd, Rg1, Rg3, and compound K significantly suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These authors demonstrated that the transformed compound exhibited a 30% increase in pancreatic lipase inhibition compared to the former saponins. The enhanced lipase inhibition caused by deglycosylation has also been confirmed for ginsenosides Rg3 and cK, both of which are triterpenoid glucosides with a single glucose moiety attached (Li & Ji, 2017). Other authors have evidenced the lipase inhibition of two dammarane-type triterpenoids derived from the acid hydrolysate of Gynostemma pentaphyllum saponins, but the bioactivity of the latter ones was not assessed (Bai et al, 2010).…”
Section: Comparative Effect Of Non-hydrolyzed and Hydrolyzed Extracts...mentioning
confidence: 98%
“…These authors demonstrated that the transformed compound exhibited a 30% increase in pancreatic lipase inhibition compared to the former saponins. The enhanced lipase inhibition caused by deglycosylation has also been confirmed for ginsenosides Rg3 and cK, both of which are triterpenoid glucosides with a single glucose moiety attached (Li & Ji, 2017). Other authors have evidenced the lipase inhibition of two dammarane-type triterpenoids derived from the acid hydrolysate of Gynostemma pentaphyllum saponins, but the bioactivity of the latter ones was not assessed (Bai et al, 2010).…”
Section: Comparative Effect Of Non-hydrolyzed and Hydrolyzed Extracts...mentioning
confidence: 98%
“…The biological activities of ginseng have been largely attributed to ginsenosides produced by different processing methods and/or biotransformation by human intestinal bacteria [16,17,24]. Although Rb1 is the most abundant ginsenoside in ginseng root and white ginseng, red ginseng produced by a steaming process substantially increases the concentration of Rg3, which is also known to be produced by human intestinal bacteria from Rb1 [22][23][24]. Several studies have therefore been aimed at converting ginsenoside Rb1 to Rg3 by various methods, including steaming, fermentation, or acidic and enzymatic treatments [15,46].…”
Section: Discussionmentioning
confidence: 99%
“…Red ginseng is known to have a distinct ginsenoside profile compared to white and raw ginseng in the content and composition of ginsenosides [18][19][20]. In particular, red ginseng is shown to be rich in ginsenoside Rg3, which is significantly increased during the steaming process, whereas ginsenoside Rb1, the most abundant ginsenoside in ginseng root, is relatively reduced in steamed red ginseng [15,[20][21][22][23]. Recent studies have shown that ginsenoside Rb1 is deglycosylated by human intestinal bacteria or digestive enzymes and is converted to a minor metabolite form, Rg3 [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The modified compound demonstrated a significant 30% enhancement in its ability to inhibit pancreatic lipase when compared to the previous saponins. The deglycosylation of triterpenoid glucosides, which involves the removal of a single glucose moiety, has been found to result in an increased inhibition of lipase activity [42]. In a study conducted by Navarro del Hierro et al [43], it was demonstrated that a quinoa extract displayed the highest IC50 value (1.15 ± 0.15 mg/mL), which was found to be significantly greater (p = 0.001) than the IC50 value of the hydrolysed quinoa extract (0.74 ± 0.09 mg/mL).…”
Section: Effects Of Non-hydrolysed and Hydrolysed P Cambodiana Bark E...mentioning
confidence: 99%
“…a single glucose moiety, has been found to result in an increased inhibition of lipase activity [42]. In a study conducted by Navarro del Hierro et al [43], it was demonstrated that a quinoa extract displayed the highest IC50 value (1.15 ± 0.15 mg/mL), which was found to be significantly greater (p = 0.001) than the IC50 value of the hydrolysed quinoa extract (0.74 ± 0.09 mg/mL).…”
Section: Effects Of Non-hydrolysed and Hydrolysed P Cambodiana Bark E...mentioning
confidence: 99%